Effect of Allopurinol on Inflammatory Markers in Chronic Kidney Disease Patients with Asymptomatic Hyperuricaemia - Anwar, ASM Tanim; Chowdhury, Md Nizamuddin; Islam, Md Nazrul; Ahmed, Parvez Iftekher; Sweety, Sohely Ahmed; Hasan, Rafiqul (Journal of Dhaka Medical College, 2017)
This was a hospital based prospective, interventional study which included CKD stage 3- 5 patients with higher level of uric acid (male>7mg/dl, female>6mg/dl). The objective of the study was to evaluate the effect of allopurinol on inflammatory markers in patients with chronic kidney disease (stage 3-5) with asymptomatic hyperuricaemia. One hundred and twenty patients were distributed in two groups. Sixty patients were placed in treatment group and sixty in control group. Purposive sampling technique was followed. In the study mean age was 49 (±9) years in treatment group and 45 (±11) years in control groups. Male were predominant in both groups. There were no significant difference in baseline characteristics between treatment group and control group (p>0.05). Sixty patients of treatment group were administered a dose of 100 mg/d of allopurinol. Follow up assessment was done at basally, at 4 months and at 8 month after starting treatment. No significant differences were seen between baseline SBP, DBP, Hb and HbA1c with 4th month and 8th month follow up in both treatment group and control group, but mean Hb was significantly decreased in control group from the baseline after 8 month. No significant change was found in case of mean ESR at 4th and 8th month in any group. But base line mean CRP was significantly reduced in treatment group and increased in control group at 4th and 8th month of follow up. Serum uric acid was decreased in treatment group while it was significantly raised from the base line at 4th month and 8th month in control group. While comparing between two groups results showed means of serum uric acid and CRP were significantly decreased in treatment group compared to control group after 8th month. There was a positive correlation between Uric Acid with CRP level after 8 month of allopurinol treatment although this finding was not statistically significant. So, allopurinol may have a protective role in CKD by decreasing serum uric acid level and reduction of inflammatory response in patients with chronic kidney disease stage 3 - 5 with asymptomatic hyperuricaemia. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 12-24